Audyt systemu informatycznego rachunkowości - Kowalska, Marianna; Kowalski, Marcin (Audit of Accounting Information System, 2005)
In the paper some chosen problems from the range of audits of accounting information systems has been presented. Having the core business of the information system illustrated, the authors focus on the legal requirements concerning the audit. An appropriate documentation is a very significant element of performing such an audit. The auditor's documentation has been deeply described in the publication.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 159-165